MUSTAQIL ISH KASBIY TA’LIMNING YANGI SIFATIGA ERISHISH OMILLARIDAN BIRIDIR - Гафурова Хакимак.ф.н.,доцент (International Scientific and Current Research Conferences, 2023)
In the article, the author talks about the role and importance of students’ independent work in the educational process. An attempt is made to study the methodological principles of organizing independent work and to highlight the main aspects of its organization.